Women and the city, women in the city : a gendered perspective to Ottoman urban history - Maksudyan, Nazan, 1977- (Berghahn Books, 2014)
An attempt to reveal, recover and reconsider the roles, positions, and actions of Ottoman women, this volume reconsiders the negotiations, alliances, and agency of women in asserting themselves in the public domain in late- and post-Ottoman cities. Drawing on diverse theoretical backgrounds and a variety of source materials, from court records to memoirs to interviews, the contributors to the volume reconstruct the lives of these women within the urban sphere. With a fairly wide geographical span, from Aleppo to Sofia, from Jeddah to Istanbul, the chapters offer a wide panorama of the Ottoman.